ANALISIS FAKTOR-FAKTOR YANG MEMEPENGARUHI KEBIJAKAN DIVIDEN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2010-2013) - Nurkholis Nurkholis; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
This research aims to analyze the influnce of investment opportunity set, profitability, free cash flow and collaterializable assets on the dividend policy. The population of this research are all manufacturing companies that listed in Indonesian Stock Exchange (IDX) during 2010-2013. The sample was selected using purposive sampling method and obtined one hundred twenty five firms being sampled. This research analyzes the company’s annual report using the method of content analysis. Data analysis used descriptive statistics, assumption tests, and tobit regression model.The result of this study showed that investment opportunity set, profitability and free cash flow significantly influence to the dividend policy. Meanwhile, collaterializable assets had no effect to dividend policy.